The soybean production frontier and economic efficiency in Mato Grosso do Sul, Brazil - Richetti,Alceu (2003)
This work evaluates the economic efficiency of productive resource utilization in the cultivation of soybeans in the state of Mato Grosso do Sul, Brazil. The study area comprises the states main soybean producing counties. Economic efficiency was estimated for a sample of 151 soybean producers through the production frontier function. The producers in the states northern region are operating near the established production frontier, signaling a favorable tendency in resource reallocation and achieving efficiency.